Sleep disorders and quality of life of medical students during martial law - Ogorenko Вікторія; Shornikov Андрій (Psychosomatic Medicine and General Practice, 2023)
Actuality. Military conflicts in general have a negative impact on the mental health of the population. It has been established that approximately every fifth person in post-conflict situations suffers from severe mental disorders. Anxiety and depression have the greatest impact on the psyche of the population, which has been determined since the first days of the war. Long-term persistence of anxiety and depression can lead to the appearance of other mental disorders, which, due to psychosomatic relationships, will cause sleep disturbances and the decreasing mental health component of quality of life. It was previously established that 17.1% of internally displaced persons had severe sleep disorders (10.6% severe and 6.5% very severe), and among Ukrainian refugees, 15.2% had pronounced sleep disorders (10.8% severe and 4.4% very severe). A similar situation was observed among combatants. The purpose of the work was to study the characteristics of sleep disorders during the war in Ukraine in students of higher medical education, as well as their impact on the mental health component of quality of life. Materials and methods: a four-fold one-moment cross-sectional epidemiological study using an online questionnaire on the Google Forms platform, which was shared through the educational portals of the Dnipro State Medical University. One hundred ninety-three medical students took part in the study. Data were collected 1, 3, 10 and 12 months after the start of martial law. Respondents had a median age of 20 (20;21) years, and almost three-quarters (74.6%) were women. Among those interviewed, 63.2% (61.8% of women and 67.3% of men) were not directly in the combat zone. Results. Disturbances in the feeling of rest after sleep, disturbances in falling asleep, and disturbances in the depth of sleep were detected. The expression of these violations was comparable after 1 month and after 1 year, and more pronounced in comparison with the period of 3 or 10 months. The mental health component of the quality of life was most decreased in the first month of the war with a gradual tendency towards a normal distribution of the indicator after a year due to the increase of persons who did not notice it or the violations were extremely insignificant. In the multiple logistic regression model, it was determined that when sleep depth violations are combined with being in dangerous conditions, their impact on the mental component of the quality of mental life is estimated by the following odds ratios: for sleep depth 4.09 (95% CI 1.82 – 9.17), for being in danger – 1.99 (95% CI 1.15 – 3.55). The AUC of the model was 0.66 (95% CI 0.59 – 0.73), which indicates its average predictive ability. Conclusions: It should be noted that the findings presented herein are preliminary and subject to limitations when applied to the general population. Our research indicates that students in higher medical education experienced notable sleep disturbances and mental health challenges both one month and one year following the onset of conflict in Ukraine. Our analysis identified disruptions in sleep patterns and exposure to hazardous conditions as the most significant risk factors for poor mental health outcomes.